The Influence Of Financial Literacy, Self Confidence And The Environment On Entrepreneurial Intentions In Generation Z - Khasanah, Uswatun; Setiyono, Wisnu Panggah; Supardi, Supardi (Universitas Hamzanwadi, 2024)
This research aims to determine the influence of financial literacy, self-confidence and the environment on entrepreneurial intentions in generation Z in Sidoarjo. Using the Probability Sampling technique, using a simple random sampling method in collecting research samples. The population of this study is generation Z in the Sidoarjo area with birth years 1997 - 2006 with a sample size of 128 people. This analysis method uses Structural Equation Modeling (SEM) which is measured using Partial Least Square (PLS), using the SmartPLS 3.0 data processing software application tool. The results of this research show that financial literacy has no impact on entrepreneurial intentions because the T-count is 1.011 (<1.96) with a significance value of 0.312 (>0.05). This shows that financial literacy has no effect on entrepreneurial intentions. Meanwhile, self-confidence has an impact on entrepreneurial intentions, because the T-calculation result is 5.252 (>1.96) with a significance value of 0.000 (<0.50). This shows that self-confidence has a positive influence on entrepreneurial intentions. And the environment has an impact on entrepreneurial intentions, with a T-count result of 2,031 (>1.96) with a significance value of 0.043 (<0.50). This shows that the environment also has a positive and significant influence on entrepreneurial intentions.